A dimensão cultural como construção social incorporada: um estudo na prática de secretariado executivo da Sicredi do oeste paranaense - Bíscoli, Fabiana Regina Veloso (2017)
Understanding social reality has always been the aim of academic studies. With the advent of modernity, organizations have become the crux of social life. Therefore, the approximation of Organizational Studies with Social Studies has provided the construction of theories capable of explaining the relationships that insert the organizational practices in the process of social organization. It is from Silvia Gherardi's theory of organization practice that this research sought to understand the cultural dimension as a social construction embodied at Sicredi's executive secretariat practice in western Paraná. The objective was to constitute a theoretical proposal of cultural study in the social constructionist perspective, inserting subject and object in the social construction of reality – a negotiated process that rescues past constructions, transforming them continuously from the reflection or the simple reproduction in the situated occurrence of a new practical action. The cultural dimension is presented as a negotiated social construction that incorporates meanings in a way that the subjects perceive, classify, judge and act in the daily life based on these constructions. Bodies demonstrate a significant knowledge when the subject, in the context of practice, speaks, silences, looks, listens and positions himself morally and ethically in daily life. When bodies feel anguish, euphoria, joy, resentment and other emotions, they reveal meanings about the practice. This study used the qualitative approach, adopting the postinterpretative posture that allowed the researcher and the researched to reflect upon the research findings. The historical analysis of the object of study, the interpretative analysis of the situated practice and the social analysis of this practice in its conditions of production, reproduction and social transformation were carried out. In this way, it was possible to demonstrate the embodied meanings that express the practical sense of being a secretary at Sicredi. On the one hand, as a repercussion of past constructions, the reproduction of socially conceived meanings, such as the close connection with the people of higher hierarchical authority of the organizations, the reinforcement of the feminine image in the context of the practice of secretariat, the representation of relations between superiors and subordinates, and the connection with the responsibility for the control and secrecy of information were observed. On the other hand, from the perspective of practitioners, it can be noted that the transformation of the historical feminine segregation is under construction at Sicredi. This means that the role of secretaries in this context incorporates more significant and relevant actions in the context of the organization, which are defined as "more strategic actions", which gives them power and status. Thus, the secrecy and responsibility for controlling access to information and the executives whom they advise is a meaning that attributes a social status to the secretaries. This complex set of embodied meanings are noted in the way of speaking, listening, dressing, and acting in the context of practice. Executive secretaries are the trusted people in the organization; they are a reference to whom all employees turn to for information and problem solving. In this sense, they are also mediators of relationships and organizational practices. Thus, it is believed to have been possible to understand the process of cultural construction embodied in its relational, historical, discursive, ethical, aesthetic and material mediation, and with that it was demonstrated the way in which situated practices connect with social reality, reproducing and transforming socially constructed conceptions.